Knowledge and practice of the physical activity prescription by generalists and specialist physicians of the city of Kinshasa: a cross-sectional study - Emeka Bowamou Christian-Khalifa; Nkodila Natuhoyila Aliocha; Nkiama Ekisawa Constant; Divengi Nzambi Jean-Paul; Kintoki Vita Eleuthère; Longo-Mbenza Benjamin; M'buyamba-Kabang; Kianu Phanzu Bernard (BMC, 2023)
Abstract Background The health benefits of regular physical activity (PA) are well documented. However, several people in both developed and developing countries do not meet PA recommendations. Health professionals are believed to be potential PA promoters. The purpose of this study is to gain insight into general and specialist practitioners' knowledge, practices and PA prescription-related factors in private and public hospitals in Kinshasa. Methods A multicenter cross-sectional analytical study was conducted among general and specialist practitioners in the Democratic Republic of the Congo's capital using a declarative and anonymous questionnaire. Results Overall, 40.2% of the participants were interested in their patient's PA, 2.3% prescribed PA, and 0.9% did it correctly. Specialist physicians (SPs) prescribed PA more frequently than general practitioners (GP), and private hospital physicians prescribed PA more frequently than public hospital physicians. Five factors were independently associated with participants in prescribing PA: being in a private hospital increased the likelihood of prescribing PA by twofold (aOR, 1.83; 95% CI, 0.99-3.39; p = 0.055), being an SP increased the likelihood by sixfold (aOR, 6.22; 95% CI, 3.78-10.51; p = 0.000), being an internist increase the likelihood by sixfold (aOR, 5.81; 95% CI, 3.45-9.78; p = 0.000), being cardiologist by a factor of 12 (aOR, 12.91; 95% CI, 4.37-38.15; p = 0.000) and knowing the benefits of PA by a factor of 2 (aOR, 2.29; 95% CI, 1.29-4.08; p = 0.006). The most common reason given for a lack of interest in patients' PA, followed by a lack of knowledge about current PA prescribing recommendations and a lack of time. Conclusions SPs and professionals in the private health sector were the most interested in their patients' PA. A small portion of them actually prescribed it, and only a tiny proportion did it correctly. This bleak picture highlights a need to rethink the undergraduate medical curricula, especially about teachings on the importance and use of PA as a medicine in its own right in disease prevention and treatment.